Hospital admissions for acute coronary syndromes during the first SARS-CoV-2 epidemic wave: time course, patients characteristics and in-hospital mortality. (14th October 2021) - Orso, F; Casolo, G; Forni, S; Szasz, C; Di Fabrizio, V; Gemmi, F
Abstract: Background: During national lockdown (LD) fear of contagion and heath care services resources redistribution to face the COVID-19 emergency, may have affected hospital access rates as well as management and in-hospital outcomes for patients with acute coronary syndromes (ACS). Purpose: To describe changes in the incidence of hospital admissions for STE- and NSTE-ACS and related short term outcomes during the first pandemic wave in Tuscany, Italy. Methods: The Agenzia Regionale di Sanità (ARS) collects administrative data from 40 hospitals in Tuscany, serving 3.730.000 inhabitants. We analyzed hospitalization rates, clinical characteristics and in-hospital mortality of STE- and NSTE-ACS patients admitted during the first 2020 pandemic wave and compared them with those of an historical reference period (2018–2019) in 3 time intervals: A) pre-LD (Jan-Feb); B) LD (March-May) and C) post-LD (June-Sept). Results: A total of 1955 STE-ACS (mean age 69±13 years; 69% males) and 2582 NSTE-ACS (mean age 73±13 years; 65% males) admissions were recorded. Compared to the historical reference period a notable and statistically significant decrease for both STE- (−10%, p<0.0001) and NSTE-ACS (−17.9%, p=0.004) was observed (Figure). Among STE-ACS hospital admissions, the greatest reduction was observed during B (−23%, p<0.0001), particularly in the month of April (−35.2%) and persisted, just missing statistical significance (−7%, p=0.08), during C. Among NSTE-ACS a similar behavior could be observed with the greatest reduction during B (−34%, p<0.0001) and a peak in the month of March (−43.3%). Interestingly, a significant decrease was observed both during A (−12.4%, p=0.004) and continued during C (−7%, p<0.04). Analyzing mean age and gender as well as baseline main clinical characteristics (eg. diabetes, heart failure, Charlson comorbidity score) no differences could be observed among STE- and NSTE-ACS patients between the two observation periods (2020 vs 2018–2019). Interestingly the percentage of STE-ACS patients presenting through the Emergency Medical System increased significantly (+10%) while no change was seen for the rate of those with a FMC to catheterization lab wire crossing <120 min. In Hospital mortality rates were 7.7% and 2.7% for STE-ACS and NSTE-ACS respectively and did not differ with those observed in the historical refence period. Conclusions: We found a marked reduction in ACS hospitalizations during the first pandemic wave compared to the same period of observation in the previous two years. This decline was present for both groups of ACS, but was more pronounced for patients presenting with NSTE-ACS and persisted to some extent in the post-lockdown period. Nevertheless, our data show that the process of care was granted as usual for the management of ACS patients who gained access to the emergency network during the first pandemic wave and in-hospital mortality did not increase. FUNDunding Acknowledgement: Type of funding sources: None.